Family and Marital Counselling In Centres For Social Work in Bosnia and Herzegovina: Challenges and Policy Implications - Dudić-Sijamija, Anida (Ревија за социјална политика/Journal of Social Policy, 2024)
Working with families is one of the most important tasks for the social work profession. In primary prevention, the most crucial task is to develop humane relationships among marital partners. Additionally, an essential segment of preventive social work involves educating and preparing youth for marriage and family and educating them about responsible parenthood. In secondary prevention, an important task of social workers is to help overcome marital conflicts. This highlights that family and marital counseling is one of the key tasks of social workers. Using QCA, the capacities of five centers for social work in Bosnia and Herzegovina in conducting marital and family counseling were analyzed. The experiences of counseling experts (N=10) were compared through semi-structured interviews. Various challenges and problems were identified that prevent centers for social work from being leaders in counseling. Family and marital counseling represents a complex and responsible task that requires expertise and competencies. The lack of systemic solutions, inconsistent norms and standards, and limited capacities of centers for social work slow down the development of quality counseling in Bosnia and Herzegovina. The data indicates that serious progress is needed in organizing the service, multi-sectoral cooperation, and institutional promotion for family and marital counseling to gain the place it deserves in social work